Alesiella gen.n. and a newly discovered relict lineage of Staphylinini (Coleoptera: Staphylinidae). (15th July 2013) - BRUNKE, ADAM J.; SOLODOVNIKOV, ALEXEY
Abstract This study aimed to identify the sister group of the poorly known and morphologically isolated Burmese species Quedius lineipennis within the tribe Staphylinini (Staphylinidae: Staphylininae) using morphological characters. Phylogenetic analysis of a broad taxon sample demonstrated that this Asian species is not a member of the genus Quedius but forms the sister taxon to the Neotropical genus Quediomacrus. Both taxa were shown to be members of a hitherto unrecognized lineage with a highly disjunct distribution. The lineage is hypothesized to be Asian in origin, with dispersals to the Americas during the early Eocene climatic maximum via Beringia and to Australia via land connections in the late Miocene. The current distribution of the lineage is considered to be relictual. New phylogenetic hypotheses within 'Quediina' and Staphylinini as a whole are proposed and the general tree topology of Staphylinini recovered by recent morphological studies is refined. Phylogenetic relationships within the Quedius complex remain unclear. Alesiella Brunke and Solodovnikov gen.n., is erected for Quedius lineipennis and the Quedius subgenus Quedionuchus is reinstated to genus level with new combinations as follows: Quedionuchus atl (Smetana, 1975), comb.n.; Quedionuchus calli (Smetana, 1976), comb.n.; Quedionuchus cipactli (Smetana, 1976), comb.n.; Quedionuchus coatl (Smetana, 1976), comb.n.; Quedionuchus ehacatl (Smetana, 1976), comb.n.; Quedionuchus ollin (Smetana, 1976), comb.n.; Quedionuchus ozomatli (Smetana, 1975), comb.n.; Quedionuchus reitterianus (Bernhauer, 1944), comb.n.; Quedionuchus samuraicus (Bernhauer and Schubert, 1916), comb.n.; Quedionuchus schultzei (Smetana, 1975), comb.n.; Quedionuchus tecpatl (Smetana, 1976), comb.n.; Quedionuchus xochitl (Smetana, 1976). Quedius lugubris Lokay, 1913 is transferred from the subgenus Quedionuchus to the subgenus Distichalius and placed in synonymy: Quedius punctatellus (Heer, 1839) = Quedius lugubris Lokay, 1913, syn.n. This published work has been registered in ZooBank, http://zoobank.org/urn:lsid:zoobank.org:pub:9C7D3C90‐FCB9‐414F‐911B‐194A1A6602DE.